The Representation of Divinity in Erna Suminar’s Collection of Sufi Poems: A Roland Barthes Perspective: Representasi Ketuhanan dalam Kumpulan Puisi Sufistik Karya Erna Suminar Perspektif Roland Barthes - Putrie Mauladanin Azama; Fardini Auralia Jauzaa; Aqilla Ghina Nur Hidayah; Shinta Aulia Munandar; Atiqotul Fitriyah (The Future of Education Journal, 2026)
This study examines the representation of divinity in Erna Suminar’s Sufi poems Mahakarya Ilahi, Pesan Rahasia, and Karena Engkau using Roland Barthes’ semiotic perspective. The research is motivated by the importance of understanding how religious and spiritual meanings are constructed through poetic symbols in contemporary Indonesian literature. The objective of this study is to describe the denotative, connotative, and mythical meanings that construct representations of God in the selected poems. This research employed a descriptive qualitative method with Roland Barthes’ semiotic approach. The data source was Pertemuan Antologi Puisi Sufistik by Erna Suminar, while the data consisted of words, phrases, and poetic expressions containing signs related to divinity. Data were collected through reading and note-taking techniques and analyzed through the stages of denotation, connotation, and myth. The findings reveal that the representation of divinity is constructed through various symbolic systems. In Mahakarya Ilahi, God is represented as the Creator and the source of human existence through artistic symbols. In Pesan Rahasia, God is portrayed as a refuge, a source of inner peace, and the destination of spiritual longing through symbols of secrecy and communication. In Karena Engkau, God is represented as the source of beauty, compassion, and power manifested through nature and human spiritual experiences. At the mythical level, the three poems construct the belief that humans can discover meaning, peace, and spiritual awareness through their relationship with God. These findings demonstrate that divinity in Erna Suminar’s poetry is represented as the center of existence, spirituality, and human life.